PENGARUH PREFERENSI PENGGUNAAN TANGAN TERHADAP KEMAMPUAN VISUOSPASIAL PADA MAHASISWA DI INSTITUT TEKNOLOGI SUMATERA - Mutia Tri Passa; Yanti Ariyanti; Winati Nurhayu; Andy Darmawan (Institut Pendidikan Tapanuli Selatan, 2024)
Handedness is a human asymmetry defined as the preference for using one hand to perform unimanual activities. It has been associated with various cognitive abilities, including visuospatial skills. Visuospatial ability is interpreted as an individual's capacity to understand the relationship between the visual and spatial aspects of a specific object in two or three dimensions and space. Institut Teknologi Sumatera (ITERA) is one of the state universities primarily focused on science and technology, requiring students to develop their visuospatial skills. This research aims to analyze the differences in visuospatial ability between students with a preference for using the right hand and those with a preference for using the left hand at Institut Teknologi Sumatera. The study utilized interview methods through handedness questionnaires, visuospatial ability questionnaires, and hand strength measurements using a hand dynamometer. The respondents in this research numbered 393 individuals, aged between 17-23 years. The study revealed that there were 30 left-handed individuals, comprising 18 males and 12 females. Ambidexterity was found in 11 males and 13 females, subsequently categorized as left-handed in the analysis. The results of the visuospatial ability test indicated that the average scores of left-handed respondents were better than those of right-handed respondents (46.39 > 43.39). Male respondents exhibited superior visuospatial ability compared to females (estimate: 1.3798; p-value: 0.0272).